Has the Department of Veterans Affairs Found a Way to Avoid Racial Disparities in the Evaluation Process for Kidney Transplantation?. Issue 6 (June 2017) - Freeman, Michael A.; Pleis, John R.; Bornemann, Kellee R.; Croswell, Emilee; Dew, Mary Amanda; Chang, Chung-Chou H.; Switzer, Galen E.; Langone, Anthony; Mittal-Henkle, Anuja; Saha, Somnath; Ramkumar, Mohan; Adams Flohr, Jareen; et al.
Abstract : Background: Minority groups are affected by significant disparities in kidney transplantation (KT) in Veterans Affairs (VA) and non-VA transplant centers. However, prior VA studies have been limited to retrospective, secondary database analyses that focused on multiple stages of the KT process simultaneously. Our goal was to determine whether disparities during the evaluation period for KT exist in the VA as has been found in non-VA settings. Methods: We conducted a multicenter longitudinal cohort study of 602 patients undergoing initial evaluation for KT at 4 National VA KT Centers. Participants completed a telephone interview to determine whether, after controlling for medical factors, differences in time to acceptance for transplant were explained by patients' demographic, cultural, psychosocial, or transplant knowledge factors. Results: There were no significant racial disparities in the time to acceptance for KT [Log-Rank χ 2 = 1.04; P = 0.594]. Younger age (hazards ratio [HR], 0.98; 95% confidence interval [CI], 0.97-0.99), fewer comorbidities (HR, 0.89; 95% CI, 0.84-0.95), being married (HR, 0.81; 95% CI, 0.66-0.99), having private and public insurance (HR, 1.29; 95% CI, 1.03-1.51), and moderate or greater levels of depression (HR, 1.87; 95% CI, 1.03-3.29) predicted a shorter time to acceptance. The influence of preference for type of KT (deceased or living donor) and transplant center location on days to acceptance varied over time. Conclusions: Our results indicate that the VA National Transplant System did not exhibit the racial disparities in evaluation for KT as have been found in non-VA transplant centers. Abstract : This study from 4 transplant centers associated with the U.S. Department of Veterans Affairs shows that there were no racial disparities in the time from first evaluation to listing for a kidney transplant. Supplemental digital content is available in the text.